Avaliação em estudos de futuros de setores industriais na perspectiva da teoria ator-rede. Estudo de caso: Observatórios da Indústria do Sistema Federação da Indústria do Estado do Paraná (FIEP) - Bolzani Júnior, Geraldo Morcel (2017)
As it is difficult to find many researches and publications about future studies evaluation, this thesis has as its objective the proposal of a future studies evaluation method for industrial sectors based on some elements of the actor-network theory. The bibliographic review shows that, in the context of future studies, the concept of ontology given to future images and visions allow the proposal of the concept of future translation. With the translation concept and observing the prospective projects of the Industry Observatory of the FIEP System, three fundamental steps of the future translation process must be considered: the expected future translation where the production, consume and discharge of expected future are analyzed, the planned future translation where the sectorial industry futures are planned and will be implemented, and the evaluated futures translation, object of this thesis. In order to accomplish this last step, the next methodological step was the design and realization of an expert panel focused on the evaluation of the prospective project of Paraná energy sector, using the sociology of expectation, strategic prospective and actornetwork theory. The actor-network methodological approaches, specially the Assemblage method were used to analyze the panel results. As the translation process was applied to the evaluation, it became dense, looking not only to the results and impacts, but also to the constitution questions of the process that will be evaluated. The evaluation expands as considering all the steps of the prospective method. The general objective of the research was accomplished as the (in the sense that was presented the) FOURMI (Ontological Fundaments Used in Industrial Mediators Networks) method was presented to produce translated evaluation in strategic prospective projects. The FOURMI method brings forward three stages: the external evaluation to summon actors that will form the actor-network, the internal evaluation to construct the formation and development processes of the actor-network, the relational evaluation to evaluate the political consequences of what was accomplished. From the method proposal, the concepts of maximum expression of actors and translated evaluation can also be extracted. Translated evaluation is the evaluation where the actants in the future translation process have their manifestations guaranteed and registered.